(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The present study aims to investigate self-confidence among higher secondary school teachers in the Ukhrul District of Manipur. The objective of the study was to determine the level of academic anxiety among higher secondary school teachers in Ukhrul District, Manipur, based on their gender, marital status, and school variation. The investigator employed a Descriptive Survey method. The study population consisted of teachers teaching in classes XI and XII from the Ukhrul District, Manipur, under the Council of Higher Secondary Education, Manipur (COHSEM). The study sample consisted of 50 participants, selected using Simple Random sampling. The questionnaire technique is employed, which is a widely used and cost-effective method for collecting quantitative data. A questionnaire is a set of questions arranged in a sequence and intended to be self-administered. The score ranged from 0-4. It has positive and negative statements. The statistical techniques used for data analysis are ANOVA, Mean, Standard Deviation, t-test, and Pearson Correlation Coefficient. The findings reveal that the majority of secondary teachers in the Ukhrul District, Headquarters, Manipur, experience an average level of self-confidence. No significant differences were observed across gender, marital status and school variation.